A jeśli uczeń wie więcej – trudna interakcja na zajęciach z języka specjalistycznego - Kic-Drgas, Joanna (Neofilolog, 2017)
Interaction between the learner and teacher in the context of Foreign Language for Specific Purposes (FLSP) is characteristic in that often the learner has greater specialist knowledge than the teacher for reasons of experience, or because they work professionally in the field. The purpose of this article is to define the factors impacting on this relationship and analyze possible difficulties for the teacher. The empirical part describes a pilot study with the aim of analyzing responses from eight FLSP teachers.